المسجد ودوره في تحقيق الأمن المجتمعي - معروفي مهاد (University of Eloued جامعة الوادي, 2024)
"العنوان: المسجد ودوره في تحقيق الأمن المجتمعي يعتبر المسجد مركزا دينيا وثقافيا واجتماعيا داخل المجتمع فقد ازداد الاهتمام بدوره في تحقيق الأمن في السنوات الأخيرة لأن الأمن المجتمعي حاجة ماسة يسعى الفرد والمجتمع لتحقيقه. هدفت هذه الدراسة إلى التعرف على الأدوار التي يقوم بها المسجد في تحقيق الأمن داخل المجتمع، وذلك من خلال الدور التعبدي، الدور التربوي، الدور التعليمي. إلى جانب ذلك يهدف البحث إلى معرفة أهم الوسائل التي يستخدمها المسجد في تحقيق الأمن داخل المجتمع والتحديات التي تواجهه. وللتطرق للدراسة انطلقت من إشكالية: كيف يتجسد دور المسجد في تحقيق الأمن المجتمعي؟ ومن النتائج المتوصل إليها: أن المسجد له أدوار متعددة للقيام بدوره في تحقيق الأمن المجتمعي، الدور التعبدي من خلال الصلاة والاعتكاف، والدور التربوي من خلال التربية الإيمانية والتربية الأخلاقية، والدور التعليمي من خلال حلقات تحفيظ القرآن الكريم وتعليم الفقه والسيرة النبوية. "Title: The mosque and its role in achieving community security. The mosque is considered a religious, cultural and social center within society. Interest in its role in achieving security has increased in recent years because community security is an urgent need that the individual and society seek to achieve. This study aimed to identify the roles played by the New Neighborhood Mosque in achieving security within society, through the worship role, the educational role, and the educational role. In addition, the research aims to know the most important means used by the mosque in achieving security within society and the challenges it faces. To address the study, it started from the problem: How is the role of the mosque embodied in achieving societal security? Since the study was descriptive, it relied on the descriptive analytical method. Among the findings: that the mosque has multiple roles to play its role in achieving community security: the devotional role through prayer and seclusion, the educational role through faith education and moral education, and the educational role through sessions for memorizing the Holy Qur’an and teaching jurisprudence and the biography of the Prophet. "
Keywords: المسجد- الأمن المجتمعي; The mosque - community security